PROS AND CONS OF DIGITAL MARKETING (Web of Technology: Multidimensional Research Journal, 2024)
Digital marketing has become an essential tool for businesses of all sizes to reach their target audience and grow their customer base. While online marketing offers many benefits, it also has its drawbacks. In this article, we’ll explore the pros and cons of digital marketing to help businesses make informed decisions about their marketing strategies. From increased reach and cost-effectiveness to privacy concerns and saturation, we’ll examine the advantages and disadvantages of digital marketing. Whether you’re a small business owner or a marketing professional, understanding the pros and cons of digital marketing can help you develop effective strategies and achieve your marketing goals.